Soft-bottom portuguese continental shelf polychaetes: diversity and distribution - Martins, R. (2018)
This study fulfills a gap in the knowledge of the annelid polychaete fauna from most of the Western Iberian coast, a particular biogeographic area where boreal, cold temperate, warm temperate and subtropical faunas can co-occur. A total of 145 samples covering the entire Portuguese continental shelf were analyzed to study the diversity and spatial distribution of the polychaetes and to discuss the relationship between biological and environmental data. A total of 19,731 annelid polychaetes were identified corresponding to 319 species and belonging to 49 families. The species Mediomastus fragilis, Polygordius appendiculatus and Ampharete finmarchica were the most abundant and Ampharete finmarchica, Lumbrineris lusitanica and Aponuphis bilineata the most frequent. Abundance per site reached 620 individuals and alpha diversity ranged from 1 species to 65 spp. 0.1m-2. A total of 26 species were firstly recorded in the Portuguese shelf, one of them new for the Iberian coasts. A multivariate analysis based on the abundance of polychaetes revealed six affinity groups: (a) coarse sediments characterized by several species, mostly of the Order Phyllodocida, such as Pisione remota, Goniadella gracilis, Glycera lapidum, Sphaerosyllis bulbosa and Pisione parapari; (b) near shore shelf fine sands dominated by Magelona johnstoni, Magelona filiformis and Sigalion mathildae; (c) northwestern deep muddy sands characterized by Prionospio fallax, Lagis koreni and Owenia fusiformis; (d) southwestern deep muddy sands with Aphelochaeta sp., Galathowenia oculata and Monticellina heterochaeta; (e) southern midshelf muddy sands characterized by Euchone rubrocincta, Prionospio multibranchiata and several southern species; and (f) muds dominated by Nepthys incisa and characterized by Sternaspis scutata, Heteromastus filiformis, Ninoe armoricana and Glycera unicornis. Sediment grain-size and organic matter were the variables best related to the benthic polychaete spatial distribution patterns along the Portuguese continental shelf.